STRATEGI PENINGKATAN PARTISIPASI PEMILIH PADA PEMILIHAN KEPALA DAERAH KOTA BANJARMASIN MENGGUNAKAN ANALYTICAL HIRERARCHY PROCESS - Agni Grandita Permata Sari; Ni Made Wijayanti Kusuma Ardani (Fakultas Politik Pemerintahan IPDN, 2023)
Abstract Voter participation in the Banjarmasin City elections has decreased from 65.63 percent in 2015 to 55.7 percent in 2020. This study aims to identify various supporting and inhibiting factors, as well as formulate the best strategy to increase voter participation in the next period. This research is a descriptive-qualitative study involving informants who were determined purposively, namely: commissioners and heads of the General Election Commission (KPU) division, and various informants from the Voting Organizing Group (KPPS) and voter groups who were determined by snowball technique. In addition, survey is also used and the data is analysed using the Analytical Hierarchy Process (AHP) to determine the priority strategy. This study found that the spread of the Covid-19 virus and bad weather which technically affected regional election activities reduced the level of voter turnout in the Banjarmasin City regional head election. Meanwhile, regulations and legal products, election administration resources, funding, and facilities/infrastructure are the supporting variables in increasing participation. The KPU of Banjarmasin City has three initiatives, namely ‘village care on elections’ program, election information socialization on print-media, and socialization through social media to increase voter participation. Of the three strategies, 'Villages care on elections' is the priority strategy for encouraging engagement, according to the findings of an analysis using AHP. Keywords: Analytical Hierarchy Process, voter participation, local election, election commission.